A formação corporal de Pedagogas para a atuação com bebês na creche - Gouvea, Maria Luiza de Andrade (Universidade Federal de São Carlos, 2025)
Body education in the Pedagogy course represents an essential axis for the re-education of the bodies of future teachers, so that they can work on building pedagogical proposals in which the body is recognized as fundamental in the interactions, play, arts, and learning of children. Considering dance and movement as expressive and liberating languages, this study aims to investigate how body awareness education in the Pedagogy degree course contributes to future teachers planning and developing movement experiences with babies aged 0 to 3 years in daycare. The research, of a qualitative and bibliographic nature, was developed through the survey, selection, and analysis of scientific productions on dance, body, education, and teacher training in the SciELO database, the CAPES Periodicals Portal, and the institutional repositories of USP and UNESP. The process involved critical reading, note-taking, and organization of references into thematic axes that allowed the identification of conceptions of body and movement present in the initial training of teachers. The theoretical analysis was articulated with reflection on the discipline "Education, Body and Movement" of the Pedagogy course at UFSCar Sorocaba campus, whose theoretical studies, practical experiences, and reflections favored the understanding of the body as a formative and pedagogical subject. The study focused on the analysis of dance experiences with babies as a way to enable dialogue between theory and practice. The results indicate that although gaps still exist in teacher training in body awareness, bodily and artistic experiences in the Pedagogy course enhance self-knowledge, sensitivity, creativity, and attentive listening, promoting more affective and humanizing practices. It is concluded that body awareness training is indispensable for consolidating a pedagogy in movement, based on integrality, freedom, and sensitivity in educational relationships.
The bodily formation of pedagogues for working with babies in daycare
Keywords: Formação de professores; Teacher education; Corpo; Body; Dança; Dance; Pedagogia; Pedagogy; Educação infantil; Early Childhood Education; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade